Additions to the millipede family Caseyidae. II. Martenseya, a new genus of miniature, blind millipedes from California (Diplopoda, Chordeumatida, Striariidea, Striarioidea, Caseyidae) - Shear, William A. (Zootaxa, 2021)
A new genus, Martenseya, is described for Martenseya minutocaeca n. sp., a tiny, blind species in the family Caseyidae from Marin County, California, USA. A key to the chordeumatidan families of northwestern North America is provided, as well as a key to caseyid genera.